PENGARUH SENAM LANSIA TERHADAP TEKANAN DARAH PADA WANITA LANSIA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS BANJARSARI METRO UTARA TAHUN 2018 - Yuli Yantina; Ajeng Saputri (Jurnal Farmasi Malahayati, 2019)
Physical changes that occur in the elderly, especially women who have entered menopause include the cardiovascular system with increased blood pressure. Elderly Gymnastics is a form of physical activity that can reduce blood pressure. The aim of the study was to determine whether there was an influence of elderly gymnastics on blood pressure reduction in elderly women with hypertension in the Banjarsari Health Center working area in 2018. This research is pre-experiment using the Two Group Posttest Design design. The sample of 60 elderly women who will be divided into two groups, namely 30 people in the intervention group and 30 people in the group. The research instrument was measurement of blood pressure (stethoscope) and observation sheet for the implementation of elderly exercises. The statistical test used is the T Test with a significance level of 0.05. The mean blood pressure for the control group in systolic BP was 167.17, and diastolic 99.33. In the experimental group systolic 160.83 and diastolic blood 94.67. Statistical test of the influence of elderly gymnastics on blood pressure reduction in elderly women with hypertension with p value for systolic (p value: 0.002) and diastolic (p value: 0.004). Conclusion there is the influence of elderly gymnastics on blood pressure reduction in elderly women with hypertension in the Banjarsari Health Center working area in 2018, so it can be suggested that health workers, especially midwives, to socialize elderly gymnastics to those who have not participated in elderly exercises given the influence of elderly gymnastics on blood pressure reduction.